Proposta de modelo padrão de aquisição de contrastes e estruturas (PAC-E) para avaliação dos desvios fonológicos - Giacchini, Vanessa (2015)
This research had as main objective to associate with the Standard Model of Contrast Acquisition (SCA) analysis of syllabic structure, allowing interaction between syllable structure and segmental inventory in phonological acquisition. Based on this purpose, the research sought to describe, extend and formalize the Standard Model of Structures and Contrast Acquisition (SSC-A). Also aimed to describe and analyze data on children with speech disorders based on the expanded model, and examine correlations between co-occurrences in different syllabic structure. The expansion of the SAC model was used three scales of analysis: in simple onset, Robustness Scale for Consonant Features (CLEMENTS, 2009); in the coda, Robustness Scale for Co-Occurrence of Consonant Features (LAZZAROTTO-VOLCÃO, 2009); the complex onset, Sonority Rating Scale by Clements and Hume (1995). It was evaluated data of 31 children of both sexes with speech disorder from a database. Data were analyzed using descriptive statistics and measures of correlation between variables (Pearson's Coefficient of Variation), and qualitative descriptive analysis of the phonological system, in which the sample was divided into 5 groups, made up according to the number of complete steps acquisition provided for the SSC-A model. Based on the three scales of analysis obtained the expansion and formalization of the model SSC-A for Brazilian Portuguese, which suggests that the phonological acquisition: the simple onset, occurs in four stages, being the strongest contrasts acquired before the less robust; the coda, also occurs in four stages, with the final positions preceding the medial during acquisition, except with the non-lateral liquid in which the acquisition is concurrent; the complex onset, occurs in two stages, starting with the acquisition of the first consonant of the complex onset and at a later stage, the field of structure, regardless of the class of segments. The analysis of 31 subjects based on SSC-A model, found that all had acquired the contrast between sonorant X obstruent, labial features in the context of stops and the contrastive in the class nasal. The class in which there was greater difficulty in establishing contrasts was in the liquid, and the liquid most affected non-lateral. The coda with archiphoneme /N/ and /L/, and the end position with archiphoneme /S/ not demonstrated difficulties, unlike with the medial archiphoneme fricative, and coda with archiphoneme /R/ that proved difficult. In complex onset, it was observed that most children have opted for deletion of the second filler component of the complex onset. It was found that there is no relationship between the domain earliest contrasts and acquisition of more complex syllable structures. And the analysis of the correlations of different syllabic constituents has identified that there is no relationship between the increase of positive co-occurrences in simple onset and increased positive correlations in other syllabic constituents. Thus, it is concluded that the description with SSC-A model allows the speech therapist view the difficulties are present only at segmental level, only the prosodic level, or both. This enables the therapist to conduct a thorough evaluation.